2004
DOI: 10.1192/apt.10.3.216
|View full text |Cite
|
Sign up to set email alerts
|

Poverty, social inequality and mental health

Abstract: The World Health Organization has described poverty as the greatest cause of suffering on earth. This article considers the direct and indirect effects of relative poverty on the development of emotional, behavioural and psychiatric problems, in the context of the growing inequality between rich and poor. The problems of children in particular are reviewed. Targets to reduce inequality have been set both nationally and internationally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
209
1
17

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 343 publications
(233 citation statements)
references
References 33 publications
6
209
1
17
Order By: Relevance
“…Depression in poor children younger than 18 years has been linked to substance abuse, poor academic performance, teen childbearing, and unemployment. 132 Poor children also are more likely to be diagnosed with conduct disorders 133 and attentiondeficit/hyperactivity disorder. 134 Substance abuse, including alcohol and tobacco, is higher for poor adolescents, increasing the risk of emphysema and cirrhosis as well as cancer.…”
Section: Compromised Mental Health Behavioral Health and Relationalmentioning
confidence: 99%
“…Depression in poor children younger than 18 years has been linked to substance abuse, poor academic performance, teen childbearing, and unemployment. 132 Poor children also are more likely to be diagnosed with conduct disorders 133 and attentiondeficit/hyperactivity disorder. 134 Substance abuse, including alcohol and tobacco, is higher for poor adolescents, increasing the risk of emphysema and cirrhosis as well as cancer.…”
Section: Compromised Mental Health Behavioral Health and Relationalmentioning
confidence: 99%
“…From the broader health fi eld, studies have established an inverse relationship between income and psychological wellbeing (Adler et al, 1994;Murali and Oyebode, 2004) and have documented improvements in mental health following the alleviation of harsh economic conditions (Leventhal and Brooks-Gunn, 2003). A growing body of work also has revealed that, net of the effect of socioeconomic disadvantage, racial discrimination is associated with poorer mental health among minorities (Finch et al, 2000;Gee, 2002;Jackson et al, 1996;Williams et al, 1997).…”
mentioning
confidence: 99%
“…Υπάξρεη κηα ζεηξά εξεπλώλ πνπ δείρλεη ηε ζπζρέηηζε αλάκεζα ζηελ ςπρηθή πγεία θαη ηνπο ρακεινύο θνηλσληθνύο -νηθνλνκηθνύο δείθηεο. Φακειά εηζνδήκαηα θαη δύζθνιεο θνηλσληθέο ζπλζήθεο ζε ζπλδπαζκό κε ηε κε πξόζβαζε ζε ππνζηεξηθηηθέο ππεξεζίεο απνηεινύλ παξάγνληεο άγρνπο θαη θξίζεσλ ζηελ νηθνγέλεηα θαη επεξεάδνπλ ηα παηδηά (Murali & Oyebode, 2004). Η θηώρεηα θαη ε θνηλσληθή αληζόηεηα είλαη ζεηηθά ζπλδεδεκέλα κε ηηο ρακειέο εθπαηδεπηηθέο επηδόζεηο θαη ειιείκκαηα ζηηο γλσζηηθέο δεμηόηεηεο ησλ παηδηώλ (Duncan, 1997).…”
Section: δηζαγσγήunclassified